Adherence of oral streptococci to nanostructured titanium surfaces. Issue 12 (December 2015) - Narendrakumar, Krunal; Kulkarni, Mukta; Addison, Owen; Mazare, Anca; Junkar, Ita; Schmuki, Patrik; Sammons, Rachel; Iglič, Aleš
Highlights: We compared adherence of oral Streptococci to titanium nanotubules. We showed that adherence increased with nanotubule diameter. Adherence was also correlated with surface fluoride content. Adherence of oral streptococci can be modified by titanium anodization. Abstract: Objectives: Peri-implantitis and peri-mucositis pose a severe threat to the success of dental implants. Current research focuses on the development of surfaces that inhibit biofilm formation while not inferring with tissue integration. This study compared the adherence of two oral bacterial species, Streptococcus sanguinis and Streptococcus mutans to nanostructured titanium surfaces. Methods: The samples included TiO2 nanotubes formed by anodization of titanium foil of 100, 50 and 15 nm diameter (NT15, NT50, NT100), a nanoporous (15 nm pore diameter) surface and compact TiO2 control. Adherent surviving bacteria were enumerated after 1 h in an artificial saliva medium containing bovine mucin. Results: Lowest numbers of adherent bacteria of both species were recovered from the original titanium foil and nanoporous surface and highest numbers from the Ti100 nanotubes. Numbers of attached S. sanguinis increased in the order (NT15 < NT50 < NT100), correlated with increasing percentage of surface fluoride. The lowest adhesion of S. sanguinis and S. mutans on TiO2 nanostructured surfaces was observed for small diameter nanoporous surfaces which coincides with the highest osteoblast adhesion on small diameter nanotubular/nanoporous surfaces shown in previous work. Significance: This study indicates that the adherence of oral streptococci can be modified by titanium anodization and nanotube diameter.